The effect of additional egg supplementation on vitamin and mineral fortification program on growth, cognitive development and hemoglobin in Indonesian underweight and stunting children. Issue 5 (21st June 2018) - Sudargo, Toto; Muhammad, Harry Freitag Luglio; Kandarina, Istiti; Putri, Nurul; Irianto, Sugeng Eko; Pranoto, Yosephin Anandati; Paramastri, Rathi
Abstract : Purpose: Stunting and being underweight in children are major nutritional problems especially in developing countries. The purpose of this study is to evaluate the effect of egg supplementation on a vitamin and mineral fortification program for growth, cognitive development and hemoglobin in underweight and stunted children. Design/methodology/approach: This was an experimental study using a crossover design conducted in Yogyakarta province, Indonesia. A total of 39 subjects were randomly selected from two community health centers and provided with two types of intervention: vitamin and mineral fortification sprinkle (Taburia) and Taburia with egg supplementation (Taburia PLUS). Each intervention was conducted for three months with one-month of washout period in between interventions. Findings: There were no changes in weight-for-age Z -score in Taburia and Taburia PLUS (all p > 0.05). The height-for-age Z -score was increased in Taburia PLUS ( p = 0.022) but not in Taburia ( p > 0.05). Hemoglobin level was significantly increased in Taburia ( p = 0.039) but not in Taburia PLUS ( p > 0.05). There were no significant changes in visual motoric score in Taburia, but there were slight increases in Taburia PLUS (all p > 0.05). Originality/value: The authors concluded that egg supplementation combined with multivitamins and minerals fortification program, Taburia PLUS, is beneficial to improve linear growth but not hemoglobin in stunted and underweight children.